Comparison of two ways of defining phonological words for assessing stuttering pattern changes with age in Spanish speakers who stutter - HOWELL, PETER (2004)
Phonological words (PWs) are defined as having a single word that acts as a nucleus and an optional number of function words preceding and following that act as satellites. Content and function words are one way of specifying the nucleus and satellites of PW. PW, defined in this way, have been found useful in the characterization of patterns of disfluency over ages for both English and Spanish speakers who stutter. Since content words carry stress in English, PWs segmented using content words as the nucleus would correspond to a large extent with PWs segmented that use a stressed word as the nucleus. This correlation between word type and stress does not apply to the same extent in Spanish. Samples of Spanish from speakers of different ages were segmented into PWs using a stressed, rather than a content, word as the nucleus and unstressed, rather than function, words as satellites. PWs were partitioned into those that were common to the two segmentation methods (common set) and those that differed (different set). There were two separate segmentations when PWs differed, those appropriate to content word nuclei, and those appropriate to stressed word nuclei. The two types of segmentation on the different set were analyzed separately to see whether one, both or neither method led to similar patterns of disfluency to those reported when content words were used as nuclei in English and Spanish. Generally speaking, the patterns of stuttering in PW found in English applied to all three analyses (common and the two on the different set) in Spanish. Thus, neither segmentation method showed a marked superiority in predicting the patterns of disfluency over age groups for the different set of Spanish data. It is argued that stressed or content word status can lead to a word being a nucleus and that there may be other factors (e.g. speech rate) that underlie stressed words and content words that affect the words around these PW nuclei in a similar way.